Psychometric properties of the critical care family needs inventory-emergency department - Dag, Gulten Sucu; Dicle, Aklime; Firat, Mehmet Ziya (W B Saunders Co-Elsevier Inc, 2017)
Purpose: The purpose of this study was to test the reliability and validity of the Turkish version of the Critical Care Family Needs Inventory-Emergency Department (CCFNI-ED) in Turkey. Methods: This study used a cross-sectional survey design. The questionnaire was administered to 400 family members of patients with a critical illness in an emergency department. The 40-item English version of the CCFNI-ED was translated into Turkish following the standard back-translation methodology. Confirmatory and exploratory factor analyses (CFA and EFA, respectively) were carried out using principal component analysis with varimax rotation to test the scale's construct validity. We used Cronbach's alpha to examine the CCFNI-ED's internal consistency reliability. Results: The CFA failed to confirm the original Australian factor structure for our sample. The original scale was then modified based on the EFA and the best possible fitting model was obtained for the Turkish family member sample. The Cronbach's alpha of the modified scale was 0.91 and those for the subscales ranged from 0.68 to 0.87. Conclusions: The psychometric evaluation showed satisfactory validity and reliability estimates, supporting the use of the Turkish version of the CCFNI-ED with a sample of family members of critically ill patients in an emergency department. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: Family needs; Critical illness; Nursing; Emergency service; Factor; Analysis; Psychometrics